2007
DOI: 10.1016/j.juro.2006.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Bladder Storage Function by Tamsulosin Depends on Suppression of C-Fiber Urethral Afferent Activity in Rats

Abstract: These results suggest that prostaglandin E(2) enhances the micturition reflex through C-fiber afferents and tamsulosin had an inhibitory effect on the C-fiber urethral afferent nerves, thereby improving bladder storage function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 17 publications
2
46
0
1
Order By: Relevance
“…7,13 Regarding EP1 receptor and bladder function, it is suggested that intravesical PGE2 promotes micturition reflex by stimulating C-fiber afferent nerves via EP1 receptor. 14,15 These previous studies and the present study indicate that the action of PGE2 via EP1 receptor has an important role in the development of bladder pain and urinary frequency in ulcer-type IC/BPS.…”
supporting
confidence: 69%
“…7,13 Regarding EP1 receptor and bladder function, it is suggested that intravesical PGE2 promotes micturition reflex by stimulating C-fiber afferent nerves via EP1 receptor. 14,15 These previous studies and the present study indicate that the action of PGE2 via EP1 receptor has an important role in the development of bladder pain and urinary frequency in ulcer-type IC/BPS.…”
supporting
confidence: 69%
“…Recently, it was reported that α1AR antogonists are effective in the treatment of storage symptoms [16]. This suggests that not only the α1D AR but also the α1A AR may have an important role in the development of storage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a rat model of detrusor overactivity caused by topical intraurethral application of prostaglandin E 2 , the action of tamsulosin depended on the suppression of C-fiber urethral afferent activity [2] . These studies showed that ␣ 1 -AR antagonists inhibit some part of bladder afferent nerves under pathological situations.…”
Section: Effects Of ␣ -Blockers On Afferent Pathwaysmentioning
confidence: 99%